(untitled) (Economics and region, 2025)
The article examines the essence, formation principles, and practical role of management reporting under dynamic markets and rising economic uncertainty. It emphasizes that a firm’s effectiveness directly depends on the quality of its management system and the speed of decision-making – both of which require a reliable internal information base. Management reporting is viewed as an organized subsystem of managerial information support, tailored to the business and oriented toward internal users. It provides timely, relevant, and granular data in the required dimensions. Unlike strictly regulated financial or tax reporting, management reporting is not fixed by rigid forms, which makes it a flexible tool for decisions rather than merely a channel for external disclosure. Its value rests on completeness, timeliness, methodological transparency, and comparability of metrics – achieved through aligned definitions, clear rules for allocating overhead costs, and stable reporting periods – while digitalization reinforces these advantages by automating data collection and visualization. The article reviews scholarly perspectives on management reporting, ranging from a narrow view of it as a purely internal instrument of managerial influence to a broader interpretation that integrates multiple reporting streams within a single information space. It highlights the dual nature of management reporting: it is both a source of factual information and a tool for organizational and methodological structuring of data. The paper identifies three key user groups – owners/top management, investors/creditors, and department heads. It substantiates a multi-level reporting package: operational (accumulative) reports for daily/weekly monitoring, current (consolidated) summaries for monthly budget-versus-actual and trend analysis, and final period-end materials (quarter/year) for assessing KPI attainment and overall efficiency. The proposed methodology covers needs identification, definition of principles and requirements, design of the KPI system, development of calculation and cost-allocation methods, assignment of accountability, and process automation. In sum, management reporting is presented as a working instrument of managerial controllability – combining unified rules, aligned indicators, user-appropriate presentation formats, and clear accountability – thereby strengthening business resilience in conditions of uncertainty.